2022
DOI: 10.3389/fpls.2021.767335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preharvest Methyl Jasmonate and Salicylic Acid Treatments on Growth, Quality, Volatile Components, and Antioxidant Systems of Chinese Chives

Abstract: Methyl jasmonate (MeJA) and salicylic acid (SA) regulate the production of biologically active compounds in plants and stimulate the accumulation of plant aromatic substances. However, the underlying mechanisms of how MeJA and SA influence characteristic flavor compounds and the antioxidant activity of vegetables are poorly understood. Five MeJA and SA concentrations were used to investigate the dose-dependent effects of these phytohormones on the dry and fresh weight; chlorophyll abundance; the contents of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 97 publications
(90 reference statements)
2
9
0
Order By: Relevance
“…The MeJA treatment significantly increased (2.8–47%) the phenolic content of the substrate-grown Chinese chives compared with that of SCK, and the 500 μM MeJA treatment had the most significant effect. This was consistent with our previous study, where the application of 500 μM MeJA increased the total phenol contents in Chinese chives ( 66 ). The phenolic compounds of hydroponic Chinese chives treated with 500 and 800 μM MeJA were significantly higher than those of the HCK group.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The MeJA treatment significantly increased (2.8–47%) the phenolic content of the substrate-grown Chinese chives compared with that of SCK, and the 500 μM MeJA treatment had the most significant effect. This was consistent with our previous study, where the application of 500 μM MeJA increased the total phenol contents in Chinese chives ( 66 ). The phenolic compounds of hydroponic Chinese chives treated with 500 and 800 μM MeJA were significantly higher than those of the HCK group.…”
Section: Resultssupporting
confidence: 94%
“…This was similar to the trend of changes observed in the levels of phenolic compounds after the MeJA treatment. In addition to phenolic compounds, sulfur-containing compounds ( 66 ), vitamin C ( 98 ), chlorophylls ( 99 ), carotenoids ( 100 ), and polysaccharides ( 101 ) also showed strong antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Exogenously used elicitors modulate the expression of a number of genes during plant development both under normal and stress conditions ( Horbowicz et al, 2011b ; Donati et al, 2019 ; Wang et al, 2021 ). These act as signaling molecules in response to environmental challenges and are crucial in the overproduction of important secondary metabolites, including flavonoids ( Akula and Ravishankar, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously used elicitors modulate the expression of a number of genes during plant development both under normal and stress conditions (Horbowicz et al, 2011b;Donati et al, 2019;Wang et al, 2021). These act as signaling Effect of different treatments of elicitors on total phenolic content of Silybum marianum in hydroponics.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl jasmonate and salicylic acid act as plant elicitors, which regulate the production and accumulation of biologically‐active and stress‐related metabolites. It has been shown that a preharvest treatment with MeJa and salicylic acid enhanced the commercial value of A. tuberosum by modulating its growth and the antioxidant potential of its leaves (Wang et al., 2022). Similarly, auxin and gibberellin regulate several physiological and developmental events, including responses to biotic and abiotic stresses.…”
Section: Resultsmentioning
confidence: 99%